How to Assess the Adequacy of Pension Benefits? The Case of Argentina - Durán, Facundo; Geri, Milva; González, Gisela Paula (Revista del CLAD Reforma y Democracia, 2021)
This paper aims to determine what conditions must the old-age transfers granted by the pension system meet to be considered adequate and presents indicators capable of quantifying this dimension of the pension performance. To this end, it is first analyzed what is meant by adequacy of the pension assets, summarizing two of its main requirements: 1) consumption smoothing and 2) prevention of poverty in adulthood. Regarding the first requirement, replacement rates are studied in their role as suitable indicators to evaluate consumption smoothing and the value of different variants of them in the case of the Argentine pension system is computed. Regarding the second condition, the ways of measuring poverty in people aged 60 and over are examined in depth. Finally, the magnitude of a minimum benefit for the elderly to have access to a basic food basket in Argentina is determined.
Keywords: Retirement; Pensions; Poverty; Aged; Care of Aged; Argentina